CONTRIBUTIONS OF FADAMA II IN THE PROVISION OF RURAL INFRASTRUCTURE IN SHIRA LOCAL GOVERNMENT AREA OF BAUCHI STATE, NIGERIA - Abdullahi, S.; Danwanka, H. A.; Haruna, U. (Journal of Agripreneurship and Sustainable Development, 2018)
The research examined the contributions of Fadama II in the provision of rural infrastructure in Shira Local Government Area of Bauchi State, Nigeria. A total of 120 respondents were randomly selected from eight Fadama community Associations in the various parts of the Local Government Area. Data were collected through administration of questionnaire using a five-point Likert-scale. The data collected were analyzed using a combination of statistical models, including descriptive statistics such as frequency, percentage and mean. The inferential statistics used include regression analysis and cross tabulation Chi-square. The analysis shows that the average age of the respondents was 38.37 years, 80.2% of the respondents were male with only 19.8% of them female. Most (88.6%) of the total respondents were married with the remaining respondents falling into the class of divorced and widowed. Majority of the respondent had formal education with an average household size and occupational experience of 12 persons and 19.43 years, respectively. The regression analysis also reveals that infrastructure provided by Fadama II was significant at P<0.001 in improving the occupational activities of the respondents. The Chi-square cross tabulation results of asymptotic Chi-statistic was significant at P<0.001 on the contributions of infrastructure; culverts, feeder-road, water source and market structure, only funds was not significant. Therefore, it can be concluded that the infrastructure provided has positive contribution on the respondents, even though it is not provided in sufficient quantity. In view of the above the need for more funding in the area of infrastructural development cannot be overemphasized. This is because sufficient provision of infrastructure will improve the life of the rural dwellers, reduce rural-urban migration and alleviate poverty.